Analysis on the role of picture books in children's cognitive development education - Chen, Menglin; Huang, Yu-Che (Edelweiss Applied Science and Technology, 2025)
Children’s cognitive development depends on picture books, which help children bridge visual stimuli and language acquisition. What they do in turn, this study investigates their effects on literacy, memory, problem-solving, and emotional intelligence. However, the role that pictures play in vocabulary building and comprehension has historically been subject to traditional research, leaving out an analysis of the role they play while interacting with and comprehending multimodal, interactive, augmented reality (AR), and artificial intelligence (AI)-enabled picture books. Studies in neuroscience show that using visual storytelling enhances the connections of the neural pathways related to critical thinking and creativity. In addition, culture and diversity in picture books aid the development of social cognition through the induction of empathy and the development of global awareness. Digital storytelling advancements from recent times indicate that AI can amend the content of a child’s picture book depending on its successive cognitive advancement to better customize learning. Additionally, the interactive features include voice recognition and eye-tracking technology, which provide real-time feedback in the reinforcement of comprehension skills. Educators and parents should include the use of innovative picture books to ensure that the aspects of cognitive development are addressed in early education. By using technology in new and different ways without sacrificing the pillars of storytelling through pictures, picture books can then be made into dynamic educational tools that are a precursor to what the children of tomorrow will need to learn. In this analysis, technology and literature are paired with cognitive science as a way of shaping young minds.